Are Civil Society Organizations Doing enough? Mainstreaming Civil Society Organisations in the Administration of Criminal Justice in Nigeria - Nnaji, Daniel Ikechukwu; Obiefuna, Anugo Samuel; Ezembu, Philip Nnabuike; Onuh, Paul Ani (University of Nigeria Journal of Political Economy, 2024)
Criminal justice administration is fundamental to the harmonious functioning of society and the regulation of deviant behaviour. The failure of the system of criminal justice administration in Nigeria has led to increase in crime rate, loss of confidence in the criminal justice system, and a general resort to arbitrary and extra-judicial actions by government agents and the general public. Despite the volume of work by Civil Society Organizations in the criminal justice sector, scholarly examination has largely focused on internal policy actions of government institutions within the criminal justice system, legislative actions by the national assembly, and other state-based responses. This study examines the role of CSOs in criminal justice administration in Nigeria. The study is anchored on Resource Mobilization Theory. Data from the study was collected from documentary sources and content analysis was relied on to make inference on the data.